Nicodemus. A Disciple Liberated by the Cross of the Christ from the Darkness of Fear and Disbelief - Grochowski, Zbigniew Tadeusz (The Biblical Annals, 2020)
Nicodemus, a Pharisee and one of the Jewish leaders, appears only in the Fourth Gospel. Three events in which he participates—a night meeting with Jesus (John 3:1-21), a verbal clash with members of the Sanhedrin (John 7:50-52) and a funeral, performed for Jesus together with Joseph of Arimathea (John 19:38-42)—are perceived negatively by numerous exegetes, and Nicodemus’s attitude is (sometimes harshly) criticised. However, taking into consideration the significance of all the details of the current narrative and the context of the occurring events, one should be led to the conclusion that this man, nowhere explicitly referred by the Evangelist with the term μαθητής, deserves to be called “a disciple of Christ,” who passed through the three-stage process of maturation in faith. Gradually he began to gain courage in advocating for Christ, and at the decisive moment—during Jesus’ death on the Cross—he definitely stepped out of hiding and gave a public testimony of his adherence to the Master of Nazareth. His person, through a gesture shown to the Crucified, became the locus theologicus in which Jesus revealed himself as the immortal Messiah, Prophet, and King.